Public Intention to Prepare for Earthquakes: Psychometric Prop-erties of Persian Version - Maryam Ranjbar; Ali Akbar Soleimani; Bahram Saleh Sedghpour; Farahnaz Mohammadi Shahbolaghi; Douglas Paton; Mehdi Noroozi (Tehran University of Medical Sciences, 2021)
Background: People are still not prepared for earthquakes in vulnerable areas although preparedness considered an effective way of reducing the disastrous consequences. A proper tool was needed to assess the predicting factors of mitigation behaviors in a large vulnerable community who speak Persian. This study aimed to introduce the valid and reliable Persian version of public intention to prepare against earthquakes. Methods: Translation, validation and reliability checking articulated according to the standard methodology for Forward-Backward translation and psychometric evaluation. Totally, 369 Tehran households were selected through stratified random sampling from Oct 2016 to Jun 2017. Exploratory Factor Analysis used to check the construct validity of all scales. Results: Face, content and construct validity of all scales confirmed (S-CVR: .65) and (S-CVI/Universal: .98). The finalized Persian version (69 items in 8 scales) showed good reliability over time in test-retest (ICC: .92) and high internal consistency both in the pilot (α: .94) and main studies (α: .94). No significant floor and ceiling effects were found in any of scales. Conclusion: Persian version of Earthquake Public Intention to Prepare is applicable as a valid and reliable instrument for research regarding disaster preparedness in Persian speaking communities.